2019
DOI: 10.3390/en12091786
|View full text |Cite
|
Sign up to set email alerts
|

How Does Information and Communication Technology Capital Affect Productivity in the Energy Sector? New Evidence from 14 Countries, Considering the Transition to Renewable Energy Systems

Abstract: By focusing on a distributed energy system that has been widely diffused for efficient utilization of renewable energy generation in recent years, this paper investigates the relationship between productivity growth and information and communications technology capital in the energy sector. Information and communications technology is a key factor in operating distributed energy systems in a way that balances energy supply and demand in order to minimize energy loss and to enhance capacity utilization. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A considerable number of Scandinavian and European countries are aggressively exploring possibilities of solar, wind, hydrogen and other fuel technologies (Cowell et al, 2017; Munro, 2019; Poletti & Staffell, 2021). Australia, Japan, and Canada, among others have concentrated their efforts in rehabilitating existing large/small hydropower projects and building new small hydropower plants (Fujii et al, 2019; Gunturu & Hallgren, 2017; Wang et al, 2020). Nchofoung and Ojong (2022) showed that sustainable development of African nations is a direct outcome of the cumulative impacts of natural resources, renewable energy (mainly hydropower) and good governance.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of Scandinavian and European countries are aggressively exploring possibilities of solar, wind, hydrogen and other fuel technologies (Cowell et al, 2017; Munro, 2019; Poletti & Staffell, 2021). Australia, Japan, and Canada, among others have concentrated their efforts in rehabilitating existing large/small hydropower projects and building new small hydropower plants (Fujii et al, 2019; Gunturu & Hallgren, 2017; Wang et al, 2020). Nchofoung and Ojong (2022) showed that sustainable development of African nations is a direct outcome of the cumulative impacts of natural resources, renewable energy (mainly hydropower) and good governance.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development and renewal of information and communication technology and the continuous penetration in the eld of consumption, communication consumption has become one of the important contents of daily consumption [5]. It is one of the indicators to improve people's quality of life and promote economic and social development.…”
Section: Evaluation Model Of Regional Household Consumptionmentioning
confidence: 99%